2018
DOI: 10.1186/s12906-018-2353-z
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin induces apoptosis in human oral squamous cell carcinoma SCC15 cells

Abstract: BackgroundOral and pharyngeal cancer is the most common malignant human cancers. Chemotherapy is an effective approach for anti-oral cancer therapy, while the drug tolerance and resistance remain a problem for oral cancer patients. Aloe-emodin, rhein and physcion are classified as anthraquinones, which are the main pharmacodynamic ingredients of Rheum undulatum L.. This study was undertaken to investigate whether aloe-emodin, rhein and physcion show inhibiting growth and inducing apoptosis in oral squamous cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Aloe-emodin is a derivate of emodin, which exhibits superior bioactivities in some cancers. It can inhibit cell proliferation through caspase-3 and caspase-9 activation in human oral squamous cell carcinoma SCC-15 cells [398], and induce apoptosis in human cervical cancer HeLa and SiHa cells, which is associated with glucose metabolism [399]. Another derivative of emodin, rhein, can also induce apoptosis in human pancreatic cancer Panc-1 cells, and inhibit tumor growth in pancreatic cancer xenograft mice [400].…”
Section: Emodinmentioning
confidence: 99%
“…Aloe-emodin is a derivate of emodin, which exhibits superior bioactivities in some cancers. It can inhibit cell proliferation through caspase-3 and caspase-9 activation in human oral squamous cell carcinoma SCC-15 cells [398], and induce apoptosis in human cervical cancer HeLa and SiHa cells, which is associated with glucose metabolism [399]. Another derivative of emodin, rhein, can also induce apoptosis in human pancreatic cancer Panc-1 cells, and inhibit tumor growth in pancreatic cancer xenograft mice [400].…”
Section: Emodinmentioning
confidence: 99%
“…Its property of low protein binding (~27%) and wide distribution achieved high concentrations in infected organs, such as the lungs, brain, and skin. 5,6 As a time-dependent antibiotic, the area under the curve of 0-24 h at steadystate divided by the minimum inhibitory concentration (AUC 24 /MIC) >80 and the percentage of time that the plasma concentrations surpass the MIC (%T >MIC >85%) were often used as pharmacodynamic (PD) indices [7][8][9][10] ). The steady-state trough concentrations (C ss,min ) of LNZ in the range of 2-10 mg/L were also associated with clinical response and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Arabinogalactan and curcumin have been extensively studied for their anti-cancer properties and both natural products decreased cell growth and significantly increased Bax/Bcl2 ratio as well as cleaved-caspase3 level in MDA-MB-231 human breast cancer cells [ 8 ]. Aloe-emodin derived from Rheum undulatum L. inhibited proliferation and induced apoptosis via activation of caspase-9 and caspase-3 in SCC15 cells [ 27 ]. Our results showed that 3-HBI derived from MO leaf extract inhibited SCC15 cell growth and triggered apoptosis via over-expression of cleaved caspase-3 and Bax, which down-regulated the anti-apoptotic Bcl-2.…”
Section: Discussionmentioning
confidence: 99%